Post-mortem ocular changes and time since death: Scoping review and future perspective. (May 2021) - De-Giorgio, Fabio; Grassi, Simone; d'Aloja, Ernesto; Pascali, Vincenzo L.
Highlights: PMI determination is essential in criminal investigations. Forensics researchers have focused chiefly on eye-based biochemical methods. We reviewed the literature on the post-mortem ocular-structural parameters. Some methods, like OCT, are highly promising for determining early PMI. Abstract: The forensics literature on the relationship between ocular changes and the postmortem interval (PMI) has traditionally focused on time-related variations in concentrations of metabolites and elements within the eye. However, structural changes within the eye over time deserve the same attention because there is significant evidence of their importance in determining the time since death. Therefore, we reviewed publications that provided substantial evidence on this issue. In light of our inclusion and exclusion criteria, 26 papers were eligible for review. On the basis of the ocular parameters considered, we grouped the reviewed evidence into eight thematic areas: corneal opacities, corneal thickness, drug-induced pupil diameter variations, retinal changes, segmentation of retinal vessels, intraocular pressure reduction, globe temperature and crystalline alterations. The most important and common limitations of the reviewed studies were small study populations (many were monocentric studies), absence of robust statistical methodology, use of mathematical models valid only in ideal conditions and validation only for short PMIs. Although many phenomena cannot be used to reliably estimate PMI, there is rigorous evidence suggesting that promising factors, including corneal thickness, require methodological innovations for application to forensics practice but could be used in the near future to reliably estimate the time since death.